Externalities and foreign capital in aquaculture production in developing countries - Wisdom Akpalu; Worku T. Bitew (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Most developing countries are increasingly dependent on fresh water based aquaculture (cage culture) to supplement the declining catch from capture fisheries. Yet, the competition for space between capture fisheries and cage culture, pollution generated by cage culture, and fish markets interaction effects have yet to be clearly conceptualized in a bioeconomic framework. Furthermore, the economic viability of cage culture depends on substantial investment thresholds, engendering foreign direct investment in the industry in developing countries. This paper develops a conceptual model for fresh water based aquaculture that account for (i) space allocation, pollution, and interaction of markets for fish; and (ii) foreign capital financing aquaculture production. We found that a Pigouvian tax (optimum ad valorem tax) that corrects the externalities depends on economic and biological parameters in aquaculture and capture fisheries. Correcting for the externalities results in a reduction in aquaculture production but not optimum wild catch. Furthermore, if the aquaculture is financed with foreign capital, then the Pigouvian tax equals the ratio of net to total benefit from aquaculture. Numerical values are used to illustrate the results.
Keywords: 330; aquaculture; externalities; Pigouvian tax; ad valorem tax